2009
DOI: 10.2340/16501977-0300
|View full text |Cite
|
Sign up to set email alerts
|

Use of the International Classification of Functioning, Disability and health: A literature survey

Abstract: The ICF has already made a major impact on the way in which data concerning disability are conceptualized, collected and processed. Utilization in developing countries must be encouraged. The addition and clarification of certain codes should be considered by the World Health Organization. There is a clear need for a classification of personal factors to allow for complete reporting on the experience of disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
1
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(127 citation statements)
references
References 221 publications
(102 reference statements)
5
109
1
10
Order By: Relevance
“…Finally, two papers were included in the category 'other': Jelsma's literature review [6] and a paper by Schuntermann on the experience with ICF in Germany [210].…”
Section: Conceptual Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, two papers were included in the category 'other': Jelsma's literature review [6] and a paper by Schuntermann on the experience with ICF in Germany [210].…”
Section: Conceptual Papersmentioning
confidence: 99%
“…However, we lack precise information about the impact the ICF has had on research. In 2009, Jennifer Jelsma produced a literature survey on the utilisation of the ICF [6]. She concluded that the ICF has already made a major impact on the way in which data concerning disability are conceptualised, collected and processed.…”
Section: Introductionmentioning
confidence: 99%
“…In another systematic review, Jelsma 40 concluded that the ICF, over the past few years, made a big impact on how data on deficiency and disability are conceptualized, collected and processed. He stressed that the classification has been used in various disciplines, health conditions, sectors and settings, and that the use of the ICF in developing countries should be encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these researchers were part of WHO's ICF Collaborating Centre for Research in Germany, which has been one of the driving forces in Europe for implementation and dissemination of the ICF since 2004 and supports its pension scheme in the standings, despite initial difficulties in translating its concepts and construction (38).…”
Section: Discussionmentioning
confidence: 99%